Effectiveness of Squatting Position on the Duration of Labor and Maternal Satisfaction among Primi Gravida Mothers: A Mixed Method Approach - Rose Prasad, Itisha; Awasthi, Prachi (International Journal of Nursing Research, 2023)
Background: Maternal positioning affects all views of labor including the power, passenger, passage, and the psyche. The position of the woman during the labor could be freely modified according to her desires and comfort. Aim: The aim of the study was to evaluate the effectiveness of squatting position on the duration of first stage of labor and the maternal satisfaction with the position. Materials and Methods: A mixed method approach was adopted and the duration of active phase of labor was assessed for the 40 samples. In-depth interview was taken to explore the concern and satisfaction of the mothers with the squatting position. Results: Major findings of the study revealed that the mean duration of the active labor of the experimental group was 224.75 min ± 15.96 while that of the control group was 253.25 min ± 27.24. The mean difference was calculated to be 28.25 and the standard error was found to be 7.06. At the level of P < 0.005, the computed “t” value was 4.03 at the degree of freedom 38. Thus, as per the analysis, squatting position was found to be effective in reducing the duration of active phase of labor. During the qualitative analysis, five themes emerged were experience of mothers, effectiveness of squatting position, issues while squatting, respectful care during the childbirth, and recommendations. Conclusion: The study illustrates that most of the primi-gravida mothers had positive attitude toward squatting and preferred supportive squatting. The study concluded that squatting is an effective position which needs to be encouraged during active labor.